2014
DOI: 10.1002/jso.23561
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for proper management of surgical drains following pancreaticoduodenectomy

Abstract: A combination of CRP levels and the color of surgical drain fluid, not POD1 or 3, but on POD 4, may be the most accurate indicators for safe drain management following PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…1). 10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Six studies included analysis of postoperative day 3 procalcitonin analysis, [20][21][22][23][24][25] eight studies day 3 C-reactive protein analysis. Five studies included analysis of CRP of day 4.…”
Section: Resultsmentioning
confidence: 99%
“…1). 10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Six studies included analysis of postoperative day 3 procalcitonin analysis, [20][21][22][23][24][25] eight studies day 3 C-reactive protein analysis. Five studies included analysis of CRP of day 4.…”
Section: Resultsmentioning
confidence: 99%
“…30 The usefulness of CRP as an early marker of complications has recently been shown during the first 4 days after pancreatoduodenectomy. [14][15][16][17][18][19][20] However, in major abdominal surgery, the accuracy of CRP has been shown to significantly increase per day after surgery. 31 Generally, 48-72 h after a single stimulus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that both CRP and WBC are useful in the early detection of complications after pancreatoduodenectomy. [14][15][16][17][18][19][20] To our knowledge, no prior study has compared the diagnostic value of CRP and WBC during the early postoperative phase after pancreatoduodenectomy. Therefore, we aimed to determine whether CRP or WBC is superior in the detection of major complications and POPF during the first seven days after pancreatoduodenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…After pancreatic reconstruction, an end‐to‐side hepaticojejunostomy and end‐to‐side duodenojejunostomy or gastrojejunostomy were made in an antecolic Roux‐en Y fashion. All patients had two closed drains (Soft Pleats Drain, Sumitomo, Bakelite Co.) placed at the time of surgery, one at the site of pancreaticogastrostomy and hepaticojejunostomy . During the study period, adjuvant GS chemotherapy (gemcitabine 700 mg/m 2 on day 1 and oral S‐1 65 mg/m 2 for 7 consecutive days, followed by a 1‐week pause) was administered to patients who met the following institutional criteria: older than 20 years, an ECOG performance status of 0‐1, adequate bone marrow reserve (white blood cell count > 3000/mm 3 , platelet count > 100 000/mm 3 , hemoglobin level > 8.0 g/dL), and adequate renal (serum creatinine concentration < 1.5 mg/dL) and liver function (total serum bilirubin concentration < 3 mg/dL) …”
Section: Methodsmentioning
confidence: 99%